Francis of Assisi : a new biography - Thompson, Augustine (Cornell University Press, 2012)
In this authoritative and engaging new biography, Augustine Thompson, O.P., sifts through the surviving evidence for the life of Francis using modern historical methods. The result is a complex yet sympathetic portrait of the man and the saint.